A User Experience and Usability Test on Playing Games Specified as Graph Grammars in GrameStation - Silva, Júlia Veiga da; Silva Junior, Braz Araujo da; Foss, Luciana; Cavalheiro, Simone André da Costa (Anais do Workshop sobre Educação em Computação (WEI), 2022)
GrameStation is a game engine based on Graph Grammar, a formal language used to describe systems and verify properties. Despite being intuitive, understanding a Graph Grammar may not be trivial for those who do not have previous experiences with this formalism. Therefore, we propose an experiment to analyze the support given by GrameStation during the running of games modeled as Graph Grammars in order to facilitate this understanding. We analyzed three groups of people with different levels of knowledge about Graph Grammar. They played two games in the platform and answered a questionnaire. It was found that the greatest difficulty was in understanding how to make the mappings to progress in the game and, as a consequence, the addition of tutorials in the platform was mentioned by several participants.